2013
DOI: 10.1021/ie402047v
|View full text |Cite
|
Sign up to set email alerts
|

Flame Retardancy and Mechanism of Bismaleimide Resins Based on a Unique Inorganic–Organic Hybridized Intumescent Flame Retardant

Abstract: To completely overcome three critical disadvantages of traditional intumescent flame retardants, a unique hybridized intumescent flame retardant (HPSi-IFR) with three-dimensional structure was synthesized, which has amine groups and Si and P elements. HPSi-IFR has very high thermal stability under either a nitrogen or air atmosphere. With a small addition of HPSi-IFR, the modified bismaleimide/diallyl bisphenol A (BDM/DBA) resin has significantly improved flame retardancy. With only 5 wt % addition of HPSi-IFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 66 publications
0
32
0
Order By: Relevance
“…This revealed that the addition of PCB-BN could form a cross-linked network with excellent thermal and dimensional stability, and the structure could protect the internal resin from further degradation. 61 It is conrmed by the FTIR spectra (Fig. 14d).…”
Section: Flame Retardant Property Of the Compositesmentioning
confidence: 94%
“…This revealed that the addition of PCB-BN could form a cross-linked network with excellent thermal and dimensional stability, and the structure could protect the internal resin from further degradation. 61 It is conrmed by the FTIR spectra (Fig. 14d).…”
Section: Flame Retardant Property Of the Compositesmentioning
confidence: 94%
“…Figure 5b and Table 3 show that the THR curve of PC/HSPCTP3 composites is lower than that of pure PC, and the THR value decreased from 71.56 to 59.11 MJ/m 2 . This is attributed to the fact that the PTFE formed a network structure after mixing and to the decomposition of HSPCTP, which contains phosphazene and hydroxypropyl silicone oil groups [32,33,34,35,36,37,38]. These results show that HSPCTP has a synergistic flame-retardant effect with PTFE, and that HSPCTP plays a major role in flame retardancy.…”
Section: Resultsmentioning
confidence: 89%
“…As Table 3 reveals, the average value of effective heat combustion (EHC) for PC/HSPCTP3 is 15.90 MJ/kg, which is smaller than that of pure PC. This phenomenon occurs because HSPCTP contains phosphazene and dihydroxypropyl silicone oil groups, which produce noncombustible gases, such as NH 3 , CO 2 , H 2 O and volatile phosphide during the combustion process [32,33,34,35,36,37,38]. Finally, the average value of HRR for PC/HSPCTP3 is 131.93 kW/m 2 , which is also smaller than pure PC.…”
Section: Resultsmentioning
confidence: 99%
“…9,10 It has been used in wave-transparent composites, 9,[11][12][13][14][15][16][17] composite laminates, adhesives, semiconductor packaging, and other applications. 13,[18][19][20][21] However, the cured resin has high crosslinking density and poor impact resistance, which makes the cyanate ester matrix undesirable in many applications. 22 Researchers have been working to toughen cyanate ester and broaden its use.…”
Section: Introductionmentioning
confidence: 99%